Impedance matching for the reduction of signal reflection in high speed multilevel three-dimensional integrated chips - 刘晓贤 朱樟明 杨银堂 王凤娟 丁瑞雪 (Journal of semiconductors, 2014)
In high speed three-dimensional integrated circuits （3D ICs）, through silicon via （TSV） insertion causes impedance discontinuities along the interconnect-TSV channel that results in signal reflection. As demonstrated for a two-plane interconnect structure connected by a TSV, we incorporate an appropriate capacitance at the junction to mitigate the signal reflection with gigascale frequencies. Based on 65 nm technology and S-parameter analysis, the decrease of signal reflection can be 189% at the tuned frequency of 5 GHz. Extending this method to the five-plane interconnect structure further, the reduction of signal reflection can achieve 400%. So we could broaden this method to any multilevel 3D interconnect structures. This method can also be applied to a circuit with tunable operating frequencies by digitally connecting the corresponding matching capacitance into the circuit through switches. There are remarkable improvements of the quality of the transmitting signals.